2010
DOI: 10.1158/0008-5472.can-09-4428
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide siRNA Screen for Modulators of Cell Death Induced by Proteasome Inhibitor Bortezomib

Abstract: Multiple pathways have been proposed to explain how proteasome inhibition induces cell death, but mechanisms remain unclear. To approach this issue, we performed a genome-wide siRNA screen to evaluate the genetic determinants that confer sensitivity to bortezomib (Velcade (R); PS-341). This screen identified 100 genes whose knockdown affected lethality to bortezomib and to a structurally diverse set of other proteasome inhibitors. A comparison of three cell lines revealed that 39 of 100 genes were commonly lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 35 publications
15
76
0
Order By: Relevance
“…42 Interestingly, Asf1b is one of the proteins involved in the activity of bortezomib, although its precise function requires further validation. 43 Taken together, these results indicate that miR-214 interferes in the replication process of myeloma cells.…”
Section: Discussionmentioning
confidence: 75%
“…42 Interestingly, Asf1b is one of the proteins involved in the activity of bortezomib, although its precise function requires further validation. 43 Taken together, these results indicate that miR-214 interferes in the replication process of myeloma cells.…”
Section: Discussionmentioning
confidence: 75%
“…When used simultaneously, BI-D1870 showed limited additive effect in combination with currently available agents, such as bortezomib, adriamycin, and melphalan. Because c-MYC is required to realize cell death by bortezomib (40,41), it may be preferable to administer RSK2 inhibitor following bortezomib for effective myeloma cell killing. In this connection, our data showed no cross-resistance between bortezomib and RSK2 inhibitor, thus suggesting that drugs that target RSK2 Ser227 may be beneficial for eliminating residual myeloma cells following bortezomib exposure.…”
Section: Inhibition Of Rsk2mentioning
confidence: 99%
“…28 In addition, recent data showed that silencing individual proteasome genes including PSMA5 and PSMB2/3/7 sensitized multiple myeloma cells to bortezomib. 29,30 However, similar data in connection with PSMB1 is not reported thus far.…”
Section: Discussionmentioning
confidence: 64%